Murder Ballads: Nick Cave and His Approach to Killing in Song. Issue 2 (3rd July 2017) - Newman, Daniel
Abstract : Violence and murder have a strong cultural currency, the implications of which should be pursued by those with an interest in law and society, crime, and justice. Murder ballads are songs about death and killing with a history stretching back to the nineteenth century. Drawing out the major themes of this genre can help scholars gain a handle on how murder has been treated in popular culture, thereupon providing an enhanced understanding of the human condition. As an example of such examination, 2016 marked the twentieth anniversary of Nick Cave and the Bad Seeds' Murder Ballads, their most famous and, perhaps, defining album. More than any other Bad Seeds album, Murder Ballads captures the essence of a band at its most comfortable in exploring the dark and the taboo: violence, killing, death. In producing a whole album on murder, the band left a calling card by which the wider public could define them. This article will explore the album by considering its key themes and, in so doing, reflect on the need to understand the use of murder in such popular music. The use of murder and death in popular music has not been properly studied, yet it offers potential social insight for several fields of study such as law, criminology, and psychology. In particular, little considered issues around the treatment of murder in popular culture such as humour are identified, while others that require greater attention such as attitudes to women are also given due consideration.